2018
DOI: 10.18632/oncotarget.24700
|View full text |Cite
|
Sign up to set email alerts
|

Plasma thymidine kinase-1 activity predicts outcome in patients with hormone receptor positive and HER2 negative metastatic breast cancer treated with endocrine therapy

Abstract: The aim of this study was to investigate if thymidine kinase-1 (TK1), a well-known proliferation marker, could represent a valid circulating biomarker to identify hormone receptor positive (HR+)/HER2 negative (HER2neg) metastatic breast cancer (MBC) patients most likely to benefit from endocrine therapy (ET). We used the DiviTum™ assay to analyze TK1 activity in cell lysates of three HR+/HER2neg BC cell lines and in plasma of 31 HR+/HER2neg MBC patients receiving ET. Blood samples were collected at treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
6
28
2
Order By: Relevance
“…When evaluating changes at longer follow-up we found that decreasing sTK1 levels from 3-6 months correlated significantly to improved survival (PFS and OS). This is in line with previous studies reporting that decreasing TK1 activity levels are predictive of prognosis in patients with MBC 14,16,17 . Bonechi et al reported an improved PFS in patients with HR+/HER2-MBC showing decreasing TK1 activity levels during ET 14 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When evaluating changes at longer follow-up we found that decreasing sTK1 levels from 3-6 months correlated significantly to improved survival (PFS and OS). This is in line with previous studies reporting that decreasing TK1 activity levels are predictive of prognosis in patients with MBC 14,16,17 . Bonechi et al reported an improved PFS in patients with HR+/HER2-MBC showing decreasing TK1 activity levels during ET 14 .…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with previous studies reporting that decreasing TK1 activity levels are predictive of prognosis in patients with MBC 14,16,17 . Bonechi et al reported an improved PFS in patients with HR+/HER2-MBC showing decreasing TK1 activity levels during ET 14 . That study only included 31 patients where 10 patients had received previous treatment for MBC and hence cannot be directly compared to our present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study concluded that the analysis of TK1 activity level along with CTC count may be used as a potential prognostic, predictive, and monitoring marker to endocrine therapy for these tumor types. 178 180 These studies showed the potential of liquid biopsy components as a tool for predicting recurrence and prognosis. More validation studies are needed to confirm the clinical applications of these non-invasive liquid biopsy methods in predicting prognosis among breast cancer patients.…”
Section: Predicting Recurrence and Prognosis In Breast Cancermentioning
confidence: 98%
“…Using a refined enzyme‐linked immunosorbent assay, the researchers observed high baseline TK1 activity level and high CTC count in metastatic cases who had worse progression‐free survival rates, as well as lower response to endocrine therapy. The study concluded that the analysis of TK1 activity level along with CTC count may be used as a potential prognostic, predictive, and monitoring marker to endocrine therapy for these tumor types . Recently, in 2018, a study by Mastoraki et al investigated ESR1 epigenetic silencing and its impact on response to endocrine therapy.…”
Section: Utilization Of Liquid Biopsy For Breast Cancer In the Clinicmentioning
confidence: 99%